2018
DOI: 10.1159/000493418
|View full text |Cite
|
Sign up to set email alerts
|

Iris Morphological Features in Patients with 360° Angle-Closure Neovascular Glaucoma: An Anterior Segment Optical Coherence Tomography Study

Abstract: Purpose: To investigate iris morphological features in 360° angle-closure neovascular glaucoma (NVG) by swept-source anterior segment optical coherence tomography (ASOCT). Patients and Methods: In this retrospective, clinic-based, comparative study, 14 patients with 360° angle-closure NVG and 14 healthy age-matched control subjects were enrolled. All patients enrolled had no prior glaucoma surgery but underwent cataract surgery with intraocular lens implantation. Horizontal scanning images of swept-source ASOC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 13 publications
0
4
0
Order By: Relevance
“…Second, our method for the measurement of IT[5,6,7] (i.e., measured from the edge of the pupil) and that used also by Invernizzi A et al,[10] (i.e., measured at the thickest point) were different from those employed in other previous studies[4,8,11] (i.e., measured near the angle). However, the root of the iris exhibits variations.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Second, our method for the measurement of IT[5,6,7] (i.e., measured from the edge of the pupil) and that used also by Invernizzi A et al,[10] (i.e., measured at the thickest point) were different from those employed in other previous studies[4,8,11] (i.e., measured near the angle). However, the root of the iris exhibits variations.…”
Section: Discussionmentioning
confidence: 99%
“…In our analysis, the IT was measured from the edge of the pupil in line with the hyperreflective line at the bottom of the iris. The IT was measured twice at 1 and 2 mm (± 0.005 mm) from the edge of the pupil (Fig 1A) used in our previous study,[6,7] and the mean of two measurements was used for subsequent analysis. The eyes of children with large mydriasis in the dark room condition were not suitable for measuring IT because the distal point (2 mm) from the edge of the pupil will locate the angle or cornea.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, previous studies on glaucomatous eyes have shown that a prolonged increase in the intraocular pressure in POAG eyes might reduce the iris blood volume, resulting in a lower IT. [19][20][21][22] In a histological study, 22 Kubota et al observed that patients with secondary glaucoma with high intraocular pressure had a lower parapapillary choroidal thickness than those with normal intraocular pressure, mainly due to decreased choroidal vessel diameter and choriocapillary vessel collapse. These pathological changes might have also occurred in the iris of the patients with POAG in this study.…”
Section: Resultsmentioning
confidence: 99%